A case–control study of risk factors for colorectal cancer in an African population. Issue 3 (May 2019) - Katsidzira, Leolin; Gangaidzo, Innocent T; Makunike-Mutasa, Rudo; Manyanga, Tadios; Matsena-Zingoni, Zvifadzo; Thomson, Sandie; Matenga, Jonathan A; Rusakaniko, Simbarashe; Ramesar, Raj
Abstract : The interplay between hereditary and environmental factors in the causation of colorectal cancer in sub-Saharan Africa is poorly understood. We carried out a community based case–control study to identify the risk factors associated with colorectal cancer in Zimbabwe. We recruited 101 cases of colorectal cancer and 202 controls, matched for age, sex and domicile. Potential risk factors including family history, socioeconomic status, urbanization, diabetes mellitus and previous schistosomiasis were evaluated. Conditional logistic regression was used to estimate the odds ratios associated with the different factors. Cases were more likely to have a tertiary education (32.7 vs. 13.4%, P <0.001) and a higher income (18.8 vs. 6.9%, P =0.002). After multivariate analysis, diabetes mellitus [odds ratio (OR): 5.3; 95% confidence interval (CI): 1.4–19.9; P =0.012], previous urban domicile (OR: 2.8; 95% CI: 1.0–7.8; P =0.042), previous schistosomiasis (OR: 2.4; 95% CI: 1.4–4.2; P =0.001) and cancer in a first-degree relative (OR: 2.4; 95% CI: 1.2–4.8; P =0.018) were associated independently with colorectal cancer. Our findings suggest that family history, diabetes mellitus, previous schistosomiasis and approximation to a western lifestyle are the predominant associations with colorectal cancer in Africans. This offers opportunities for targeted prevention and hypothesis-driven research into the aetiology of colorectal cancer in this population.